Cas12a target search and cleavage on force-stretched DNA. Issue 47 (8th September 2021) - Losito, Marialucrezia; Smith, Quentin M.; Newton, Matthew D.; Cuomo, Maria Emanuela; Rueda, David S.
Abstract : CRISPR-Cas12a target search and cleavage on force-stretched λ -DNA using optical tweezers. Abstract : Using optical tweezers, we investigate target search and cleavage by CRISPR–Cas12a on force-stretched λ-DNA. Cas12a uses fast, one-dimensional hopping to locate its target. Binding and cleavage occur rapidly and specifically at low forces (≤5 pN), with a 1.8 nm rate-limiting conformational change. Mechanical distortion slows diffusion, increases off-target binding but hinders cleavage.